2003 Orto y Ocaso - Grupo Teatro La Cochera (2017)
Idea: Paco Giménez | Actúan: Chacha Alvarado, Carolina Amor, Silvina Bustos Fierro, Marcelo Castillo, patricia cugat, Gabriela duran, Marola Farías, Sergio Gallego, David Gerber, Vequi Gómez, andrea gonzalez, Rita Novillo Corvalán, Lalo Orellano, Guillermo Wright | Dirección: Paco Giménez | Consultado el 8 de noviembre de 2016 http://www.alternativateatral.com/obra3992-orto-y-ocaso